A Background on System Identification in Structural Engineering Using Kalman - Oreta, Andres W.C (Philippine Engineering Journal)
System identification is an important step towards the aim of evaluating the existing condition, assessing the degree of damage and deterioration and predicting the response of structures. In this regard, this paper aims to provide the structural engineer a background on the application of system identification in the field of structural engienering using Kalman filter techniques. The basic concepts in system identification and parameter estimation are described and the linear discrete Kalman filter algorithm used to carry out the system identification is summarized. To illustrate the system identification by Kalman filter, a single degree of freedom system was analyzed. A survey of researches related to this field is also presented.